Paradigma Otonomi Khusus dan Integrasi Nasional di Papua - Yambeyapdi, Ester (Ministry of Home Affairs, 2022)
The New Order regime's way of resolving the problem of Papua's national integration did not produce desirable results. The New Order regime, with its authoritarian and centralized practices, has provided valuable lessons for the nation. This study is a review of political history that aimed to analyze the national integration issues in several areas in Papua, which has not been resolved during the 21 years of Special Autonomy in Papua. The results of the study showed that the situation of the Papuan during the New Order Regime influenced the national integration of Papuans during the Special Autonomy implementation. The issue of Papua's national integration during the New Order regime and the Special Autonomy implementation in the Reformation era was an anomaly in the truth because the truth was determined by the ruler (hegemonic authority). The special autonomy has accelerated the development of Papua, but also created discrimination between tribes and groups in social, cultural, economic, and political life. Learning from history, to avoid making the same mistakes in the future, the humanist approach taken by the church can be a solution to unify the differences between Papuan